2009
DOI: 10.1002/prot.22370
|View full text |Cite
|
Sign up to set email alerts
|

A new prediction strategy for long local protein structures using an original description

Abstract: A relevant and accurate description of three-dimensional (3D) protein structures can be achieved by characterizing recurrent local structures. In a previous study, we developed a library of 120 3D structural prototypes encompassing all known 11-residues long local protein structures and ensuring a good quality of structural approximation. A local structure prediction method was also proposed. Here, overlapping properties of local protein structures in global ones are taken into account to characterize frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

7
1

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 58 publications
5
36
0
Order By: Relevance
“…In the same way, analysis of PUs in terms of secondary structures did not show any significant tendency in comparison to the entire databank. The Protein Blocks [56,75,85,88,99,[101][102][103][104][105][106][107][108] give a finer description than secondary structures [109], they so give more precise description of protein contacts and even some insights in signature of specific regions of protein loops in the PUs (e.g., PBs h and i).…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, analysis of PUs in terms of secondary structures did not show any significant tendency in comparison to the entire databank. The Protein Blocks [56,75,85,88,99,[101][102][103][104][105][106][107][108] give a finer description than secondary structures [109], they so give more precise description of protein contacts and even some insights in signature of specific regions of protein loops in the PUs (e.g., PBs h and i).…”
Section: Discussionmentioning
confidence: 99%
“…Longer fragments based on PBs were predicted with better accuracy [166,169]. Frequently observed 11 residue fragments described based on the dihedrals were predicted with a significant accuracy of about 63% using SVMs [170]. Prediction of structural flexibility based on local structure preferences has also been successful [171].…”
Section: Beyond Secondary Structuresmentioning
confidence: 98%
“…Our earlier work on PBs have shown that PBs are effective in describing and predicting conformations of long fragments (Benros, et al, 2006; Benros, et al, 2009; Bornot, et al, 2009; de Brevern, et al, 2007; de Brevern and Hazout, 2001; de Brevern and Hazout, 2003; de Brevern, et al, 2002) and short loops (Fourrier, et al, 2004; Tyagi, et al, 2009; Tyagi, et al, 2009), analyzing protein contacts (Faure, et al, 2008), in building a transmembrane protein (de Brevern, 2005; de Brevern, et al, 2009), and in defining a reduced amino acid alphabet to aid design of mutations (Etchebest, et al, 2007). This reduced amino acid alphabet was recently proved suitable for predicting protein families or sub-families and secretory proteins of P. falciparum (Zuo and Li, 2009; Zuo and Li, 2009).…”
Section: Protein Blocksmentioning
confidence: 99%
“…This resulted in higher structural variability for the longer fragments through a significant increase in the number of prototypes, e.g ., 100 to 130 prototypes (Benros, et al, 2006; Benros, et al, 2009; de Brevern and Hazout, 2001; de Brevern and Hazout, 2003). These longer fragments were used to perform structural superimposition (de Brevern and Hazout, 2001), methodological optimisation (Benros, et al, 2003; de Brevern and Hazout, 2003), and analysis of sequence – structure relationship (Benros, et al, 2006; Benros, et al, 2009; Bornot, et al, 2009; de Brevern and Hazout, 2001). A modified version of HPM proposed by Pr.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation